Turbulent Airflow and Thermal Analysis in a Circular Tube Heat Exchanger Fitted With Turbulence‐Inducing Vortex Generators (X‐V Baffles) - Boonloi, Amnart; Jedsadaratanachai, Withada (Modelling and Simulation in Engineering, 2025)
The research presents an investigation into airflow configuration, thermal behavior, and convective heat transfer enhancement in a circular heat exchanger tube fitted with turbulence generators. These turbulence generators, referred to in this study as X‐V baffles (XVBs), were developed to generate swirling flow within the heat exchanger tube, which is directly related to the enhancement of heat transfer rates and the overall performance of the heat exchanger. Additionally, the XVBs were designed with consideration for practical application and ease of maintenance in real‐world industrial settings. The study examines the variables influencing airflow topology and thermal structure, including the blockage ratio ( g / D = 0.05–0.20), pitch ratio ( P / D = 1–2), flow direction (FD‐VD and FD‐VU), and types of turbulence generators (Type S and Type T XVBs). The research was conducted within the turbulent flow regime, with Reynolds numbers ranging from 3000 to 12,000 (Re = 3000–12000). The results are presented in terms of observed flow behavior within the test tube, such as cross‐flow streamlines, streamwise flow streamlines, Nusselt number distribution, and fluid temperature distribution. The findings clearly show the formation of swirling flow in the heat exchanger tube when XVBs are installed. An increase in the blockage ratio and a decrease in the pitch ratio lead to a more intense swirling flow. The intensity of this swirling flow is directly correlated with the degree of disturbance in the thermal boundary layer (TH‐BL). The maximum enhancements in Nusselt number and friction factor due to XVB installation are 7.24 and 58.01 times greater, respectively, compared to a smooth tube without XVBs. The maximum thermal enhancement factor (TEF) achieved is 2.27, obtained from the case with the Type T XVB at a blockage ratio of g / D = 0.05, a pitch ratio of P / D = 1, and a flow direction in the FD‐VD configuration.